The Application of Writing Skill in Arabic Writing for Students in Middle School - Pradana, Ari Sandi; Rahmaini, Rahmaini (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2024)
This study aims to reveal the application of maharah kitabah in Arabic writing of seventh grade students at MTs Uswatun Hasanah Binjai. The importance lies in the realization that writing skills in Arabic are a major component in the Arabic language learning process. This research uses a qualitative descriptive approach, namely the field study method. Respondents of this study were seventh grade students of MTS Uswatun Hasanah Binjai totaling 30 students, while the data collection techniques were observation, interview and documentation. Data processing techniques, namely data reduction, data presentation, conclusion drawing and verification. To test the credibility of the author using triangulation techniques with various data collection techniques and various data sources. The research subject focuses on the person who applies maharah kitabah, namely the seventh grade Arabic teacher of MTS Uswatun Hasanah and the seventh grade students of MTS Uswatun Hasanah Binjai. Research results found in this study are learning materials Arabic teachers use Student Worksheets (LKS) as one of the learning tools, in the learning process of maharah kitabah, teachers apply thematic methods where all learning elements are integrated in one topic in one learning session. The technique used is writing, which involves writing a simple sentence or number of sentences from the LKS material used. students do a personal demonstration of expression by doing writing exercises, starting from forming letters into words, combining words into sentences, and involving translation exercises between Arabic and Indonesian.